2018
DOI: 10.1016/j.yjmcc.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of prostaglandin E2 EP4 receptor improves cardiac function after myocardial infarction

Abstract: Overexpression of EP4 improves cardiac function post MI. This may be mediated through reductions in adverse cardiac remodeling or via inhibition of cytokine/chemokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…We further build on the findings of these past studies that link mitochondrial calcium accumulation with ROS production alongside the induction of MPT, bioenergetic collapse and necrosis both in cultured cardiomyocytes and in vivo. Importantly the work presented here also demonstrates that these pathways can be pharmacologically modulated through PGE1-induced EP4 activation, which work from us and others, has been shown to be cardioprotective (Field et al, 2018;Martens et al, 2020;Bryson et al, 2018). While a previous study has demonstrated that Bnip3 phosphorylation inhibits its interactions with OPA-1, we provide mechanistic evidence both in vivo and in cardiomyocytes that misoprostol activates the EP4 receptor and PKA, resulting in an inhibitory phosphorylation of Bnip3's TM domain at Thr-181.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We further build on the findings of these past studies that link mitochondrial calcium accumulation with ROS production alongside the induction of MPT, bioenergetic collapse and necrosis both in cultured cardiomyocytes and in vivo. Importantly the work presented here also demonstrates that these pathways can be pharmacologically modulated through PGE1-induced EP4 activation, which work from us and others, has been shown to be cardioprotective (Field et al, 2018;Martens et al, 2020;Bryson et al, 2018). While a previous study has demonstrated that Bnip3 phosphorylation inhibits its interactions with OPA-1, we provide mechanistic evidence both in vivo and in cardiomyocytes that misoprostol activates the EP4 receptor and PKA, resulting in an inhibitory phosphorylation of Bnip3's TM domain at Thr-181.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, previous work has demonstrated that prostaglandin (PG) signalling through the PG EP4 receptor, a G-protein coupled receptor classically associated with enhanced protein kinase A (PKA) activity, improves cardiac function in mice following MI (Bryson et al, 2018). Furthermore, overexpression of the EP3 receptor, known to reduce PKA activity, is deleterious in the murine heart (Bryson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot (WB) and real‐time PCR ( RT‐PCR) were carried out as previously described . Antibodies for NLRP3 and ASC were purchased from Santa Cruz Technology (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the stimulation of prostaglandin EP4 receptor by PGE 2 in an I/R model induces cardioprotective effects through the increase in IL10 secretion and inhibition of TNFα [ 67 ]. Gene therapy overexpressing prostaglandin EP4 receptor in mice subjected to MI restores cardiac function and reduces hypertrophy and fibrosis [ 46 ]. In addition, prostaglandin EP3 receptor selective activation reduces the infarct size post-MI [ 47 ].…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%